2017
DOI: 10.1016/j.rboe.2017.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Acetabular revision in total hip arthroplasty with tantalum augmentation and lyophilized bovine xenograft

Abstract: ObjectiveTo evaluate a mixed technique of acetabular reconstruction, which uses trabecular metal in the form of tantalum augments associated with lyophilized bovine xenograft.MethodsFifteen patients were evaluated prospectively, who underwent acetabular reconstruction with impacted lyophilized bovine xenograft associated with the use of tantalum augments. The main outcome was the failure of the tantalum–bone interface.ResultsThe population had a mean age of 58.33 years ± 14.27; the majority was female, 80%. Of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…Não foram relatadas reações imunogênicas ou toxicidade (Trotta et al, 2014). O comportamento histológico do enxerto ósseo bovino liofilizado foi avaliado em humanos, em cirurgias ortopédicas mostrando excelente osteocondutividade biocompatibilidade (Diesel et al, 2017;Galia et al, 2012;Ribeiro et al, 2015,). No caso relatado, os controles tomográficos demonstraram a remodelação progressiva da área com a manutenção da arquitetura óssea e incorporação do enxerto ósseo, confirmados clinicamente pela ausência de rejeição/infecção.…”
Section: Discussionunclassified
“…Não foram relatadas reações imunogênicas ou toxicidade (Trotta et al, 2014). O comportamento histológico do enxerto ósseo bovino liofilizado foi avaliado em humanos, em cirurgias ortopédicas mostrando excelente osteocondutividade biocompatibilidade (Diesel et al, 2017;Galia et al, 2012;Ribeiro et al, 2015,). No caso relatado, os controles tomográficos demonstraram a remodelação progressiva da área com a manutenção da arquitetura óssea e incorporação do enxerto ósseo, confirmados clinicamente pela ausência de rejeição/infecção.…”
Section: Discussionunclassified
“…Diesel et al used lyophilized bovine bone graft (Orthogen -Baumer) along with a tantalum wedge to reconstruct the acetabular in total hip arthroplasty in 15 patients. Authors reported comparable results to reconstructions performed using impacted grafts [63]. Charalambides et al used Surgibone (Unilab, Inc., NJ, USA), a mixture of bovine bone apatite and protein with autograft to fill defects in the acetabulum and the proximal femur in revision surgery in 27 patients.…”
Section: Xenograft-based Graft Substitutesmentioning
confidence: 99%
“…TM augments together with lyophilized bovine xenograft for hip reconstruction are proved to be effective in young patients with an average of 45.2 months follow-up. 127 Apart from the porous Ta used in hip, cups and augments made of porous Ti were also reported. Lima was the first company to popularize porous Ti acetabular cup made by additive manufacturing; other companies such as AK Medical or Smith&Nephew issued similar products since 2015 one by one.…”
Section: Application Of These Porous Metals In Different Parts Of The...mentioning
confidence: 99%
“…Combination of TM augments and other techniques is mentioned, too. TM augments together with lyophilized bovine xenograft for hip reconstruction are proved to be effective in young patients with an average of 45.2 months follow-up …”
Section: Application Of These Porous Metals In Different Parts Of The...mentioning
confidence: 99%